Market Reaction to Dividend Announcement: Evidence from Nepalese Stock Market - Adhikari, Kamal Prakash (Journal of Emerging Management Studies, 2024)
Purpose – This paper aims to evaluate the impact of dividend announcements on stock price in the Nepalese stock market under the semi-strong form of market efficiency. Design/methodology/approach – The market model of the event study method was followed to assess the impact of dividend announcements. This study was based on a quantitative research approach with secondary data which included the daily share price as the dependent variable and the NEPSE index as an independent variable. There were 20 commercial banks listed in NEPSE until the date of the study, and out of them only 17 banks were taken as samples because they have announced dividends regularly for 9 years from mid-July 2014 to mid-July 2023. Findings and Conclusion – This research concluded that abnormal returns were positive in good news and negative abnormal returns in bad news about dividend announcement. These results were statistically significant on the event day. These outcomes also supported the dividend signaling hypothesis, and information content hypothesis in the semi-strong form of efficient market hypothesis (EMH). However, with no news of dividend announcement, it has negative impacts on stock returns which were statistically insignificant. Implications – The implication of the results is that the Nepalese stock market is inefficient in the semi-strong form while considering good, bad, and no news of dividend announcements. This paper contributes to gaining more knowledge of market efficiency for Nepalese capital market investors, securities trading platform NEPSE, regulatory body SEBON, and researchers of the share market.